Pictures from a distant country : images on 19th century U.S. currency - Doty, Richard D. (Boson Books, 2004)
Everyone knows that there is only one form of American currency, the product of a single issuer. The currency is the Greenback, and the issuer is the federal government. But this arrangement has not always been the rule: for much of the nation's history (including what many would see as its most dynamic period of growth) there was no federal currency in circulation. Instead, there were the products of private banks and other businesses, which had or took upon themselves the right and responsibility to issue currency. We call this private money obsolete bank notes, and they form the basis of t.